Composición fitoquímica del aceite de las semillas del fruto del "Aguaymanto", Physalis peruviana L. - Chasquibol Silva, Nancy Ascención (2015)
The content of fatty acids and antioxidants in the oil of the seeds of fruit of "aguaymanto" were studied. The extraction of crude oil was carried out by the expeller pressing method with a yield of 18.09%. Fatty acids, tocopherols and sterols by chromatographic methods were quantified. The oil has a high percentage of ¿-6 (76.7%) with a degree of unsaturation of 77.1%. The a- tocopherols (70 ppm), ß- (1452 ppm), ¿- (1469 ppm) and d- (1445 ppm) are the main species have been separated and quantified by HPLC. Sterols d-5-avenasterol (17.1%), ß-sitosterol (9.7%), stigmasterol (4.9%) and campesterol (4.8%), are the most important species have been separated and quantified by GC. The results obtained confirm that the oil and cake extracted from the seeds of "aguaymanto" could be considerate as a source of natural antioxidants to promote good health and skin care.